Studi Numerik Aerodinamika Turbin Angin Kontra Rotasi Berdasarkan Variasi Jarak Terhadap Rasio Putaran Rotor - Akhmad Riszal; Agus Sugiri (Fakultas Teknik, Universitas Lampung, 2026)
Counter Rotating Wind Turbine (CRWT) is one of the developments of horizontal axis wind turbines that utilize two rotors rotating in opposite directions to increase the efficiency of wind energy conversion. This study aims to analyze the aerodynamic characteristics of CRWT using the Computational Fluid Dynamics (CFD) method by studying the effect of variations in the distance between the rotors on turbine performance. The blade model used consists of three blades using the S826 airfoil from the National Renewable Energy Laboratory (NREL). Simulations were carried out using the Moving Reference Frame (MRF) method with the Realizable k-ε turbulence model. The variations analyzed include the distance between the rotors Z/D₁ of 0.25 and 1 at a rotor rotation ratio of 0.6 with a Tip Speed ​​Ratio (TSR) of 6. The simulation results show that the CRWT configuration produces a higher power coefficient than a single rotor turbine. The maximum power coefficient value obtained reaches around 0.52 or an increase of 14.61% compared to the Single Rotor Wind Turbine (SRWT). The flow velocity distribution shows that the distance between the rotors affects the wake interaction and energy distribution on the rear rotor. The configuration with a distance of Z/D₁ = 0.25 produces a more uniform flow distribution, thus improving aerodynamic performance, while the distance of Z/D₁ = 1 shows a greater wake interaction so that the rear rotor efficiency decreases slightly. The results of this study indicate that optimizing the inter-rotor distance is an important parameter in improving the performance of CRWT under the same operating conditions.